Cultural capital and Black education : African American communities and the funding of Black schooling, 1865 to the present - Franklin, V. P. 1947-; Savage, Carter Julian (Emerald Publishing Limited : Information Age Publishing, 2004)
A discussion of the contributions made by African Americans to public and private black schools in the USA in the 19th and 20th centuries. It suggests that cultural capital from African American communities may be important for closing the gap in the funding of black schools in the 21st century.
Keywords: African American schools -- Finance.; Segregation in education -- Economic aspects -- United States.; Educational equalization -- United States.; Education -- Philosophy, Theory & Social Aspects.; Relating to African American, Black American people.; Philosophy and theory of education.; elektronické knihy; electronic books